2015
DOI: 10.7314/apjcp.2015.16.4.1507
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed Induces G1 Phase Arrest and Apoptosis through Inhibiting Akt Activation in Human Non Small Lung Cancer Cell Line A549

Abstract: Pemetrexed is an antifolate agent which has been used for treating malignant pleural mesothelioma and non small lung cancer in the clinic as a chemotherapeutic agent. In this study, pemetrexed inhibited cell growth and induced G1 phase arrest in the A549 cell line. To explore the molecular mechanisms of pemetrexed involved in cell growth, we used a two-dimensional polyacrylamide gel electrophoresis (2-DE) proteomics approach to analyze proteins changed in A549 cells treated with pemetrexed. As a result, twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…These findings indicate that p53 also plays an important role in the apoptotic pathway triggered by KMU-193 in A549 cells. Increasing evidence suggests a close link between induction of apoptosis in lung cancer cells and expression and/or activity of apoptosis-regulated protein, including p-Akt (Kim et al, 2013;Wu et al, 2015). Besides, it has been reported that p53 can activate the PTEN promoter leading to increased expression levels of PTEN, a negative regulator of the PI3K/Akt pathway (Feng, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that p53 also plays an important role in the apoptotic pathway triggered by KMU-193 in A549 cells. Increasing evidence suggests a close link between induction of apoptosis in lung cancer cells and expression and/or activity of apoptosis-regulated protein, including p-Akt (Kim et al, 2013;Wu et al, 2015). Besides, it has been reported that p53 can activate the PTEN promoter leading to increased expression levels of PTEN, a negative regulator of the PI3K/Akt pathway (Feng, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic cells were quantified using the Annexin V/propidium iodide (PI) double staining method and analysis of phosphatidylserine on the outer surface of apoptotic cell membranes ( 29 ). The treated 4T1 cells received 10-Gy irradiation, were harvested after 72 h, and washed twice with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, establishing a treatment model to mimic the first-line second-line treatment is important, as it can be used to confirm the known clinical trial information, to analyze the mechanism and to test other drugs in the future. The inhibitory effects of docetaxel and pemetrexed on cell proliferation have been demonstrated (18,19). The present study compared the inhibitory effect of the docetaxel-pemetrexed (Doc-Pem) group with that of the pemetrexed-docetaxel (Pem-Doc) group.…”
Section: Introductionmentioning
confidence: 99%